Ecological compensation for winter wheat fallow and impact assessment of winter fallow on water sustainability and food security on the North China Plain. (15th December 2021) - Ti, Jinsong; Yang, Yuhao; Pu, Liangliang; Wen, Xinya; Yin, Xiaogang; Chen, Fu
Abstract: The North China Plain (NCP) is one of the major grain production areas in China where the groundwater level has declined rapidly in recent years because of irrigation. To alleviate the pressure on water resources, in 2016, the government developed and implemented a reasonable subsidy policy, known as the Winter Fallow Policy (WFP), to fallow cultivated land in a selected pilot area in the funnel region (Heilonggang region, HR). In the present study, a large-scale household survey was conducted across the NCP groundwater overexploitation region (OR) to evaluate the possible impact of the WFP on groundwater and food security. Our survey results indicated that the education level of decision makers, the dependency ratio of farmers, laborers per cultivated area, and the magnitude of the importance of water-saving in agriculture of decision makers have significant impacts on farmers' willingness to fallow. The average ecological compensation (EC) was 8781 CNY/ha (1358 USD/ha) and varied from 6932 to 10816 CNY/ha (1072–1673 USD/ha) in different counties. Winter wheat fallow in semiarid, dry subhumid and humid areas can save approximately 4642, 3325 and 1906 m 3 /ha, respectively, of groundwater in the OR. In the HR, a fallow area of 0.31 × 10 6  ha is recommended for maintaining the current groundwater table, and an area of 0.42 × 10 6  ha is recommended for restoring or recovering groundwater resources; these areas are greater than the existing fallow area and will reduce wheat yields, accounting for 1.55% and 2.08%, respectively, of national wheat production. Thus, EC standards should be determined based on local commodity price standards and modified based on annual changes in local conditions. Furthermore, the winter fallow acreage should be expanded in the HR to maintain the groundwater table. Graphical abstract: Image 1